Coumarins Isolated from Murraya paniculata in Vietnam and Their Inhibitory Effects against Enzyme Soluble Epoxide Hydrolase (sEH) - Khanh, Pham Ngoc; Spiga, Ottavia; Trezza, Alfonso; Kim, Young Ho; Cuong, Nguyen Manh (Planta Medica International Open, 2016)
In the search for bioactive constituents from Vietnam medicinal plants, the leaves and stems of Murraya paniculata collected in HoaBinh Province, Vietnam were selected for chemical investigation. From the n-hexane fraction, two sterols, including β-sitosterol (6) and stigmasterol (7), and from the chloroform fraction, five coumarins, including mexoticin (1), omphalocarpin (2), murrangatin (3), kimcuongin (4), and murracarpin (5), were obtained. The structures of the isolated compounds were determined from ESI-MS, HR-ESI-MS, and NMR (1D and 2D) spectroscopic data. Coumarins (1–5) were elucidated for inhibitory effects against soluble epoxide hydrolase. Among them, coumarins (2–4) showed soluble epoxide hydrolase inhibitory activity with IC50 values 2.2 ± 4.7, 13.9 ± 6.5, and 3.2 ± 4.5 µM, respectively. A kinetic study of the five coumarins revealed the noncompetitive enzymatic mode for 3 and 4, and a mixture of competitive/noncompetitive enzymatic modes for coumarin 2. Using molecular modelling, the coumarin kimcuongin (4) showed the best binding outline into active sites of human soluble epoxide hydrolase.
Keywords: Murraya paniculata; Rutaceae; coumarin; kimcuongin; murracarpin; AutoDock/Vina; soluble epoxide hydrolase (sEH)